PENGARUH GOOD GOVERNANCE DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP PENGELOLAAN DANA DESA DENGAN RELEGIUSITAS SEBAGAI PEMODERASI - Sucahyo Heriningsih; Dwi Sudaryati (Universitas Ahmad Dahlan, 2019)
As a manifestation of the enactment of Law No. 6 of 2014 on the village, village development aims to improve the welfare of rural people and the quality of human life and poverty alleviation through the fulfillment of basic needs, development of village facilities and infrastructure, local economic development, and the utilization of natural resources and Environment in a sustainable manner. Therefore, the implementation of good governance in the village, as well as the competent human resources of the village apparatus, can support the implementation of the Village Law. Relegiusity of course becomes an important role as a benchmark of honesty of human resources (village apparatus). This study aims to examine the effect of good governance and human resource competence on the implementation of village law with relegiusitas as a moderation variable. Data were collected using questionnaires from 31 village apparatus located in the village of Banguntapan, Bantul District. The results showed that there is a good governance influence on the implementation of Village Law, while variable the competency of human resources does not affect the implementation of Village Law. Similarly, the relegiusity variable does not support the hypothesis so that relegiusity is not a moderating variable.